2014
DOI: 10.1128/jvi.02785-13
|View full text |Cite
|
Sign up to set email alerts
|

Loss of a Conserved N-Linked Glycosylation Site in the Simian Immunodeficiency Virus Envelope Glycoprotein V2 Region Enhances Macrophage Tropism by Increasing CD4-Independent Cell-to-Cell Transmission

Abstract: Human immunodeficiency virus (HIV) and simian immunodeficiency virus (SIV) strains differ in their capacity to replicate in macrophages, but mechanisms underlying these differences are not fully understood. Here, we identify a highly conserved Nlinked glycosylation site (N173 in SIV, corresponding to N160 in HIV) in the V2 region of the SIV envelope glycoprotein (Env) as a novel determinant of macrophage tropism and characterize mechanisms underlying this phenotype. Loss of the N173 glycosylation site in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 102 publications
1
26
0
Order By: Relevance
“…Because CD4-independent viruses are characteristically neutralization sensitive, it is likely that they are strongly selected against during typical pathogenic infection (32,48,49,97). Recent publications by Yen et al have suggested that CD4-independent entry serves as a mechanism of cell-cell viral spread in tissue macrophages, which is more efficient and can shield virus from neutralizing antibodies than cell-free transmission, thereby allowing CD4-independent variants to circulate in compartments such as the brain (59,60). Interestingly, primary isolates of HIV-2, which is less pathogenic than HIV-1 (reviewed in reference 98), have been reported to exhibit CD4 independence in vitro (61,99).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because CD4-independent viruses are characteristically neutralization sensitive, it is likely that they are strongly selected against during typical pathogenic infection (32,48,49,97). Recent publications by Yen et al have suggested that CD4-independent entry serves as a mechanism of cell-cell viral spread in tissue macrophages, which is more efficient and can shield virus from neutralizing antibodies than cell-free transmission, thereby allowing CD4-independent variants to circulate in compartments such as the brain (59,60). Interestingly, primary isolates of HIV-2, which is less pathogenic than HIV-1 (reviewed in reference 98), have been reported to exhibit CD4 independence in vitro (61,99).…”
Section: Discussionmentioning
confidence: 99%
“…For one neuropathic SIV isolate, its ability to cause AIDS encephalopathy in macaques correlated with the infection of brain-derived endothelial cells that expressed CCR5 but not CD4 (58). In addition, CD4-independent infection has been proposed to contribute to SIV infection of macrophages in the context of cell-to-cell transmission (59,60). Of note, viruses that are CD4 independent typically retain their CD4 binding site and the ability to engage CD4, if present (30,34,58,61,62), and have been shown to exhibit faster fusion kinetics in the presence of CD4 than CD4-dependent viruses (63).…”
mentioning
confidence: 99%
“…In contrast, recombinant gp120 displays extensive glycan processing by cellular glycosylation enzymes, resulting in glycans composed of Ͼ70% complex glycans (26,27). Studies of HIV-1 glycosylation have focused mainly on the Env structure and surface exposure and their effect on antigenicity, immunogenicity, and antibody neutralization (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) through mutation of the position of glycosylation, rather than modification of the type of glycans. Studies of the effect of glycosylation on HIV-1 infectivity and carbohydrate and receptor binding have also utilized deletion of the potential N-linked glycosylation sites (PNGSs) (15)(16)(17)(18)28).…”
mentioning
confidence: 99%
“…N-Glycans include three basic structures, namely, high-mannose (i.e., oligomannose), hybrid, and complex glycans, all of which are present on HIV-1 Env (4-7). Importantly, N-glycans shield the Env backbone and have been shown to play key roles in determining the Env structure, epitope exposure, and, consequently, antigenicity, immunogenicity, antibody neutralization, infectivity, and carbohydrate and receptor binding (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
See 1 more Smart Citation